The Role of Performance Appraisals in Motivating Employees - Jurjen J.A. Kamphorst; Otto H. Swank (Tinbergen Institute, 2012)
In many organizations, reward decisions depend on subjective performance evaluations. However, evaluating an employee's performance is often difficult. In this paper, we develop a model in which the employee is uncertain about his own performance and about the manager's ability to assess him. The manager gives an employee a performance appraisal with a view of affecting the employee's self perception, and the employee's perception of the manager's ability to assess performance. We examine how performance appraisals affect the employee's future performance. The predictions of our model are consistent with various empirical findings. These comprise (i) the observation that managers tend to give positive appraisals, (ii) the finding that on average positive appraisals motivate more than negative appraisals, and (iii) the observation that the effects of appraisals depend on the employee's perception of the manager's ability to assess performance accurately.
urn:NBN:nl:ui:15-1765/32104
Keywords: M52; M54; D82; D83; 330; Subjective Performance Appraisal; Credibility; Cheap Talk; Arbeitsproduktivität; Leistungsmotivation; Leistungsbeurteilung; Entscheidung bei Unsicherheit